2009
DOI: 10.1016/j.mce.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in pancreatic β-cells in Type 2 Diabetes

Abstract: Mitochondrial metabolism controls insulin secretion from the pancreatic β-cell. Type 2 Diabetes evolves when the β-cells fail to release appropriate amounts of insulin, causing metabolic dysregulation and hyperglycemia. It is attractive to assume that mitochondrial dysfunction plays a decisive role in these processes. Indeed, while being a rare condition, genetically determined dysfunction of mitochondria causes a Type 2 Diabetes-like syndrome.Here, we review what is known about mitochondrial dysfunction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 80 publications
0
74
0
Order By: Relevance
“…Ndufa4 is also considered to be an endogenous antioxidant that protects intracellular membranes from lipid peroxidation under oxidative stress (9). Since intact mitochondrial function is required for normal insulin secretion (12,15), low expression of Ndufa4 could lead, under conditions of exceeding demand, to mitochondrial insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Ndufa4 is also considered to be an endogenous antioxidant that protects intracellular membranes from lipid peroxidation under oxidative stress (9). Since intact mitochondrial function is required for normal insulin secretion (12,15), low expression of Ndufa4 could lead, under conditions of exceeding demand, to mitochondrial insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are implicated in the pathogenesis of diabetes mellitus (14). Recently, a connection between Pdx1 insufficiency and mitochondrial dysfunction was described, implicating dysregulation of the mitochondrial transcription factor TFAM in abnormal insulin secretion (15).…”
mentioning
confidence: 99%
“…Based on the substantial evidence that mitochondrial dysfunction is linked to insulin resistance and beta cell dysfunction, and is present in multiple tissues relevant to the pathogenesis of type 2 diabetes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], we hypothesised that common variation in OxPhos genes contributes to an increased risk of type 2 diabetes or influences metabolic traits related to the disease. OxPhos gene variants showing nominal association with type 2 diabetes in a meta-analysis of three GWA studies that were part of the DIAGRAM Study [28] were selected for follow-up in an independent cohort of Danish individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This includes reports of reduced expression of electron transport chain (ETC) genes in adipose tissue of women with type 2 diabetes [16], and of impaired mitochondrial respiratory capacity in heart muscle [17] and liver from type 2 diabetic individuals [18]. Finally, mitochondrial ATP production is known to play a critical regulatory role in glucosestimulated insulin secretion, and several recent studies have suggested that defects in mitochondrial OxPhos could contribute to beta cell dysfunction in patients with type 2 diabetes [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%